2013
DOI: 10.1249/mss.0b013e31827989ec
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Models of Acute Mountain Sickness after Rapid Ascent to Various Altitudes

Abstract: These models provide the first quantitative estimates of AMS risk over a wide range of altitudes and time points and suggest that in addition to altitude and time at altitude, high activity increases the risk of developing AMS. In addition, men demonstrated increased severity but not prevalence of AMS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
57
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 31 publications
6
57
1
Order By: Relevance
“…The major determinants of AMS are the altitude attained [22], individual susceptibility, rate of ascent and degree of preacclimatisation [13,23,24]. Therefore, prevalence of AMS depends very much on the study setting.…”
Section: Epidemiologymentioning
confidence: 99%
“…The major determinants of AMS are the altitude attained [22], individual susceptibility, rate of ascent and degree of preacclimatisation [13,23,24]. Therefore, prevalence of AMS depends very much on the study setting.…”
Section: Epidemiologymentioning
confidence: 99%
“…Thus, future studies should implement a more robust sleep questionnaire, for example, the Groningen Sleep Questionnaire and/or direct polysomnography assessments. Third, due to the relatively small numbers of questionnaire items, the effect of other potential candidate factors, such as a history of previous AMS, migraine (Richalet et al, 2012;Canouï-Poitrine et al, 2014;Vinnikov et al, 2014), body mass index (obesity) (Beidleman et al, 2013), physical activity level (Beidleman et al, 2013), physical exertion (Roach et al, 2000), current smoking status (Beidleman et al, 2013;Vinnikov et al, 2014), cardiorespiratory responses to hypoxia (Oliver et al, 2012;Richalet et al, 2012;Canouï-Poitrine et al, 2014), and hydration status, including drinking habits (Mairer et al, 2009;Oliver et al, 2012), which have been investigated previously, on AMS in this population remains uncertain. Although future studies that include these items are warranted, our results clearly demonstrated that sleeping altitude may play an important role in increasing the prevalence and severity of AMS.…”
Section: Limitationsmentioning
confidence: 99%
“…However, it appears that there are no sex differences in the rate of acclimation to altitude, the prevalence of acute mountain sickness (AMS), or in the ability to perform work while at altitude (Gore et al 1997;Hackett et al 1976). Using modelling methods applied to historical data, lower severity but not frequency of AMS were predicted for both active and inactive men than for comparably fit women (Beidleman et al 2013). The authors hypothesized that the reduced severity of AMS was possibly due to increased progesterone in premenopausal women with possible mediators of endothelial permeability and free radical production.…”
Section: Sex Differences In Response To Environmental Extremesmentioning
confidence: 99%